Common property rights and indigenous fishing practices in the inland openwater fisheries of Bangladesh: the case of the Koibortta fishing community of Kishoregonj - Rashid, Saifur (Curtin University, 2005)
Bangladesh contains one of the richest and largest inland fisheries in South Asia and the third highest inland capture fisheries in the world and has a long history, which continues to the present, of conflict and cooperation between fishers and other diverse fishing interests over access to a range of fishing environments managed under a variety of leasing and tenurial arrangements. Several fishing communities are of ancient origin and over a long period of time have developed and adapted their indigenous fishing knowledge, including technologies, fishing practices and knowledge of diverse fishing environments to manage fisheries in a variety of environmental and ecological conditions. This thesis provides a detailed ethnographic account of one such community, the Koibortta fishers of Krishnapur village in the northeast flood plain region of Bangladesh, focusing on their management practices and indigenous fishing knowledge in selected inland common property fisheries. It examines, using documentary and oral historical sources, the ways in which they have adapted aspects of their indigenous fishing knowledge to changing economic and environmental circumstances over the past 50 years. It also examines, using case studies of three water bodies, how they were able to gain short-term and insecure access to selected water bodies, partly by drawing on traditional social networks at village and multivillage levels to mobilise fishers in negotiations with leaseholders.The thesis argues that these social networks and fishers’ capacity to adapt aspects of their fishing knowledge to new circumstances were insufficient to gain long term, secure and direct access to productive water bodies as fishers lacked strong government commitment to their long term security. The thesis concludes with a discussion of the capacity of Krishnapur fishers to manage fish resources equitably and sustainably.